Genderlect Styles: Analysis Of Ibsen’s “A Doll’s House” From The Perspective Of Gender Differences In Language Use - Robina Khaliq (University of Chitral Journal of Linguistics and Literature, 2024)
This present paper examines Ibsen’s A Doll’s House from the viewpoint of gender differences in the use of language by the characters in the play, and the way the lives of the characters are affected by the use of language. The study concludes that the prevalent ideologies in the society define the gender roles that stimulate women to maintain intimacy and connection and men to preserve their independence and status. However, females break this connection when they tend to preserve their identity and individuality instead of maintaining connection. The analysis of the selected text, from the play, is carried out through using Discourse analysis tools like Identity Building Tool, Turn Taking and Holding Floor, Story Telling, Empty Adjectives, Intensifiers. Tannen’s theory of Genderlect Styles and Althusser’s concept of Ideological State Apparatuses have been used to draw the conclusion.